Dual-laser frequency-stabilized cavity ring-down spectroscopy for water vapor density measurements. (27th July 2018) - Fasci, Eugenio; Dinesan, Hemanth; Moretti, Luigi; Merlone, Andrea; Castrillo, Antonio; Gianfrani, Livio
Abstract: Absolute measurements of water vapor densities have been carried out using a new concept of frequency-stabilized cavity ring-down spectroscopy. Our scheme is based on the use of a pair of phase-locked extended cavity diode lasers, emitting at 1.39 m, one of them being locked to a self-referenced optical frequency comb synthesizer. An intrinsically stable high-finesse optical cavity that tracks the laser frequency scans has been used. High quality, comb-calibrated, absorption spectra have been recorded in a certified H2 O/N2 gas mixture at different gas pressures, in coincidence with the 2 transition of the H2   18 O   +   band. Water vapor mole fractions have been determined with a statistical uncertainty of 0.6 . Systematic deviations have been identified and carefully quantified, thus leading to an overall uncertainty of 0.8 .